2017
DOI: 10.29237/2358-9868.2017v5i2.p94-104
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da sonolência diurna e qualidade do sono em idosos e sua relação com a qualidade de vida

Abstract: Avaliação da sonolência diurna e qualidade do sono em idosos e sua relação com a qualidade de vidaEvaluation of daytime sleepiness and sleep quality in the elderly and its relation with quality of life AbstractObjective: To evaluate daytime sleepiness and sleep quality in the elderly and their influence on quality of life. Methods: Quantitative, cross-sectional and descriptive research. For the evaluation of daytime sleepiness was used the Epworth Sleepiness Scale (ESS), to evaluate sleep quality, the Pittsbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
1
0
5
Order By: Relevance
“…In the current study, excessive daytime sleepiness was higher in the elderly male (50.0% in hyperfrequent and 66.7% in non-hyperfrequent) with a significant difference. National studies showed 24.0% to 55.6% of the elderly with excessive daytime sleepiness, however, in the studied populations, female predominated, and in the current study the sexes were analyzed separately [44,45,46,47]. Thus, the presence of excessive daytime sleepiness and poor sleep quality can have a negative impact on the health and quality of life of the elderly.…”
Section: Discussionmentioning
confidence: 62%
“…In the current study, excessive daytime sleepiness was higher in the elderly male (50.0% in hyperfrequent and 66.7% in non-hyperfrequent) with a significant difference. National studies showed 24.0% to 55.6% of the elderly with excessive daytime sleepiness, however, in the studied populations, female predominated, and in the current study the sexes were analyzed separately [44,45,46,47]. Thus, the presence of excessive daytime sleepiness and poor sleep quality can have a negative impact on the health and quality of life of the elderly.…”
Section: Discussionmentioning
confidence: 62%
“…A qualidade do sono dos idosos avaliados em geral é ruim (74,5%). No estudo de Magalhães et al (2017) 18 , utilizando os mesmos instrumentos, ao avaliar 128 idosos, também encontraram 69,9% deles com má qualidade do sono.…”
Section: Discussionunclassified
“…Estes resultados podem ser associados ao fato de que o ritmo de sono-vigília é regulado por dois processos distintos: homeostático e circadiano, quando eles acontecem adequadamente, tem-se uma boa qualidade de vigília durante o dia e de sono durante a noite 18 . Alguns parâmetros ambientais atuam na regulação adequada do ritmo sono-vigília, como a exposição à luz do dia, atividade física, refeições em horários regulares e interações sociais 19 .…”
Section: Discussionunclassified
“…Em um estudo quantitativo, transversal e descritivo, com 128 idosos, que se avaliou nível de sonolência diurna através da Escala de Sonolência de Epworth, qualidade do sono através do índice de Qualidade do Sono de Pittsburgh e qualidade de vida através do WHOQOL-BREF, constatou-se que fatores como alterações intrínsecas e extrínsecas decorrentes do envelhecimento, como modificação do padrão social, padrão doméstico, redução dos ciclos de amizade, inação física e profissional contribui para uma maior sonolência diurna e, assim, um sono noturno de qualidade ruim, tendo um resultado negativo na qualidade de vida [22].…”
Section: Discussionunclassified